2019
DOI: 10.1186/s12893-019-0580-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasms of the pancreas and European guidelines: importance of the surgery type in the decision-making process

Abstract: Background The European Consensus 2018 established a new algorithm with absolute and relative criteria for intraductal papillary mucinous neoplasms of the pancreas (IPMN) management. The aim of this study was to validate these criteria and analyse the outcomes in function of the surgical procedure and IPMN subtype. Methods Clinical, radiological and surgical data (procedure, morbidity/mortality rates) of patients who underwent surgery for IPMN between 2007 and 2017. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
2
13
1
Order By: Relevance
“…Among the absolute indicators, the presence of jaundice and solid mass were shown to be significantly associated with malignancy and were proven to be the predictors of IPMN with HGD/IC, which agrees with the available literature data [14,24,30]. Although relatively new criteria was applied for the IPMN management and listed as a relative indication for the resection according to EEBGPCN, the present study confirmed increased levels of serum CA 19-9 as predictors of HGD/IC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the absolute indicators, the presence of jaundice and solid mass were shown to be significantly associated with malignancy and were proven to be the predictors of IPMN with HGD/IC, which agrees with the available literature data [14,24,30]. Although relatively new criteria was applied for the IPMN management and listed as a relative indication for the resection according to EEBGPCN, the present study confirmed increased levels of serum CA 19-9 as predictors of HGD/IC.…”
Section: Discussionsupporting
confidence: 90%
“…These guidelines introduced new relative indicators for the resection: Growth rate > 5 mm per year, new-onset diabetes mellitus, and acute pancreatitis caused by IPMN. The importance of appropriate surgical strategies in the IPMN treatment has been highlighted [13], together with the plea on including the surgery type in the decision-making algorithm [14]. Results from the study by McGinnis et al [15] on 72 pancreatic adenocarcinoma tumor resection patients showed that patients with pancreatic adenocarcinoma arising from IPMNs have a statistically significant longer overall survival and progression-free survival when compared to patients with tumors arising from pancreatic intraepithelial neoplasms, which highlight the importance of the appropriate surgical management of IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…We considered the morbidity and mortality risk associated with surgical intervention in our patient. In respect to postoperative morbidity risk, a retrospective study of patients receiving surgical intervention for IPMNs demonstrated an overall 12% rate of morbidity in patients who underwent a distal pancreatectomy with biochemical leak as the most frequently reported complication (44%) [ 14 ]. Weighing the relative risk of postoperative morbidity against recurrent pancreatitis and potential for malignant transformation as high as 10.7% [ 15 ], we believe surgical intervention was justified.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is believed that the degree of pancreatic fat infiltration increases with age, making the pancreatic anastomosis more difficult, which may lead to an increase in the incidence of POPF. 31 33 Furthermore, the degree of pancreatic fat infiltration and degree of fibrosis can affect the texture of the pancreas. 10 , 34 However, previous studies on the effects of pancreatic texture on POPF have reported different conclusions.…”
Section: Discussionmentioning
confidence: 99%